Literature Review on the Role of Teachers in Improving Student Learning Motivation - Faris Ahzamy; Muhammad Fauzan; Riska Latiful Husna (Al-Ard: Journal of Education, 2025)
This article aims to comprehensively review the role of teachers in enhancing students’ learning motivation through a literature review approach. Learning motivation is a crucial factor influencing the success of the learning process, and teachers play a strategic role in fostering and maintaining students’ motivation. The method used in this study is a literature review by analyzing various relevant academic sources, including books, journal articles, and previous research related to learning motivation and teacher roles. The findings indicate that students’ learning motivation is influenced by several key aspects, namely teachers’ emotional support, the implementation of innovative and engaging teaching methods, adaptation to students’ learning styles and needs, strengthening social relationships in the classroom, and providing constructive feedback. In addition, this review identifies challenges faced by teachers, such as limited resources and diverse student characteristics. Therefore, teachers are required to be adaptive, creative, and reflective in designing learning activities. This article is expected to contribute theoretical insights and practical recommendations for educators in creating a supportive, inclusive, and sustainable learning environment to enhance students’ learning motivation.